Characteristics Of Haloakcumulative Characteristics Of Clover Varieties (Texas Journal of Agriculture and Biological Sciences, 2023)
This article reports on the eco-biological and salt-accumulating properties of alfalfa (Medicago sativa) local "Tashkent-2009", "Kyzilkesak" and introduced "Scepter" varieties. As a result of our research, the possibility of haloaccumulation of the researched plants increases as follows: "Sceptra" → "Kyzilkesek" → "Tashkent-2009"; and it was found for the first time that the salt tolerance index decreases in the manner of Tashkent-2009→Kyzilkesek→Sceptra. Among alfalfa varieties studied on the basis of haloaccumulation indicators, "Tashkent-2009" adaptation to saline soils was noted. The results of the obtained chemical analysis show that it is appropriate to use all varieties and samples of alfalfa in phytoremediation, depending on the haloaccumulation capabilities of plants and the amount of chlorine ions in them. Also, these fodder plants have characteristics of maintaining their salinity tolerance in other soil conditions, which indicates that their salinity tolerance is a stable genetic trait.